2004
DOI: 10.1088/0953-8984/16/5/008
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in nanomagnetism and spin electronics

Abstract: This paper presents recent experimental advances in the field of nanomagnetism and spin electronics. It covers the period of the last decades during which fundamental discoveries such as giant magnetoresistance have been successfully transferred to industrial applications. Such results could be obtained thanks to the improvements of thin film deposition and lithography techniques. Present preparation efforts are now oriented towards lateral size reduction of continuous layers in order to minimize the size of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 121 publications
0
33
0
1
Order By: Relevance
“…[17]. Recently, Bobo et al described few examples of EB using MR in a review [18]. The studies of EB using MR has also been observed in very few structurally single-phase compounds [121,99,188,139,193].…”
Section: Magnetic Field Dependencementioning
confidence: 99%
“…[17]. Recently, Bobo et al described few examples of EB using MR in a review [18]. The studies of EB using MR has also been observed in very few structurally single-phase compounds [121,99,188,139,193].…”
Section: Magnetic Field Dependencementioning
confidence: 99%
“…Although ferromagnetic behaviour is observed here, both lower temperature studies and perpendicular magnetization measurements, which are not possible with the current experimental arrangement, would be needed for more detailed interpretation. For example, it is possible that the steps (figure 2(b), regions 1 and 2) have an out-of-plane easy axis [2], or a lower Curie temperature (T C ) due to increased instability to magnon formation as dimensionality is reduced [27].…”
Section: Hysteresis Loops From Au-capped Fe Nanostructures Grown On Vmentioning
confidence: 99%
“…[29][30][31][32] This versatile material has exciting properties such as transparent conduction, magnetism and resistance switching which renders its use in spintronics and resistive random access memories. [33][34][35] Recent efforts are made to evaluate the performance of nNiO in nematic LC, in which it is seen that twisted nematic LC doped with nNiO exhibited lower threshold voltage and faster response time.…”
Section: 28mentioning
confidence: 99%